Physiological Linkage in Couples and its Implications for Individual and Interpersonal Functioning: A Literature Review - Timmons, Adela C. (J Fam Psychol, 2015)
Do partners’ levels of physiological arousal become linked in close relationships? The term “physiological linkage” describes covariation between people in their moment-to-moment physiological states. The current review presents a conceptual framework to guide research on linkage in romantic relationships and discusses the potential implications of being “linked.” Evidence of linkage was found across a broad range of physiological indices and in a variety of contexts, including during laboratory-based conflict and in daily life. Four hypotheses regarding how linkage relates to individual and interpersonal functioning are evaluated: (1) co-activation of the sympathetic nervous system or hypothalamic-pituitary adrenal axis is “bad,” (2) moderate physiological linkage is “just right,” (3) physiological linkage is problematic if the individual or couple is overloaded, and (4) the implications of physiological linkage depend on the emotional context. We found partial support for the first hypothesis and determined that more research is needed to evaluate the remaining hypotheses. Linkage in cortisol was negatively associated with relationship satisfaction; but at the same time, linkage in multiple systems was positively associated with indices of relationship connectedness, such as the amount of time spent together and the ability to identify the emotions of one’s partner. These results suggest that linkage may confer benefits but also may put couples at risk if they become entrenched in patterns of conflict or stress. With research in this area burgeoning in recent years, this review indicates that linkage is a promising construct with applications for interventions targeting individual health and couple functioning.